WNK bodies cluster WNK4 and SPAK/OSR1 to promote NCC activation in hypokalemia - Thomson, Martin N. (Am J Physiol Renal Physiol, 2020)
K(+) deficiency stimulates renal salt reuptake via the Na(+)-Cl(−) cotransporter (NCC) of the distal convoluted tubule (DCT), thereby reducing K(+) losses in downstream nephron segments while increasing NaCl retention and blood pressure. NCC activation is mediated by a kinase cascade involving with no lysine (WNK) kinases upstream of Ste20-related proline-alanine-rich kinase (SPAK) and oxidative stress-responsive kinase-1 (OSR1). In K(+) deficiency, WNKs and SPAK/OSR1 concentrate in spherical cytoplasmic domains in the DCT termed “WNK bodies,” the significance of which is undetermined. By feeding diets of varying salt and K(+) content to mice and using genetically engineered mouse lines, we aimed to clarify whether WNK bodies contribute to WNK-SPAK/OSR1-NCC signaling. Phosphorylated SPAK/OSR1 was present both at the apical membrane and in WNK bodies within 12 h of dietary K(+) deprivation, and it was promptly suppressed by K(+) loading. In WNK4-deficient mice, however, larger WNK bodies formed, containing unphosphorylated WNK1, SPAK, and OSR1. This suggests that WNK4 is the primary active WNK isoform in WNK bodies and catalyzes SPAK/OSR1 phosphorylation therein. We further examined mice carrying a kidney-specific deletion of the basolateral K(+) channel-forming protein Kir4.1, which is required for the DCT to sense plasma K(+) concentration. These mice displayed remnant mosaic expression of Kir4.1 in the DCT, and upon K(+) deprivation, WNK bodies developed only in Kir4.1-expressing cells. We postulate a model of DCT function in which NCC activity is modulated by plasma K(+) concentration via WNK4-SPAK/OSR1 interactions within WNK bodies.